Vectors, Hosts, and the Possible Risk Factors Associated with Severe Fever with Thrombocytopenia Syndrome - Jin-Na Wang (Hindawi Limited, 2021)
Severe fever with thrombocytopenia syndrome (SFTS) is a disease caused by infection with the SFTS virus (SFTSV). SFTS has become a crucial public health concern because of the heavy burden, lack of vaccines, effective therapies, and high-fatality rate. Evidence suggests that SFTSV circulates between ticks and animals in nature and is transmitted to humans by tick bites. In particular, ticks have been implicated as vectors of SFTSV, where domestic or wild animals may play as the amplifying hosts. Many studies have identified antigens and antibodies against SFTSV in various animals such as sheep, goats, cattle, and rodents. Besides, person-to-person transmission through contact with blood or mucous of an infected person has also been reported. In this study, we reviewed the literature and summarized the vectors and hosts associated with SFTS and the possible risk factors.